The Struggling Trainee: Principles of Effective Remediation - Kurzweil, Arielle M.; Galetta, Steven L. (Seminars in Neurology, 2018)
Struggling trainees exist in all residency programs across all fields. Remediation, the act of improving deficiencies in struggling trainees, is necessary to promote the graduation of competent physicians. Deficiencies may be primarily cognitive or behavioral, and occasionally physical limitations do arise during residency. Remediation is challenging for all parties involved, and there is a paucity of literature to help guide the most effective process. In this review, we outline key principles of effective remediation of a struggling trainee in the modern era of medical education. A systematic approach that begins early, is consistent, and remains sensitive to a trainee's need for self-reflection in a nonjudgmental culture is essential for successfully remediating a trainee.
Keywords: remediation; feedback; milestones; mentorship; competency